2005
DOI: 10.1002/bit.20655
|View full text |Cite
|
Sign up to set email alerts
|

Production of 2‐phenylethanol and 2‐phenylethylacetate from L‐phenylalanine by coupling whole‐cell biocatalysis with organophilic pervaporation

Abstract: An integrated bioprocess for the production of the natural rose-like aroma compounds, 2-phenylethanol (2-PE) and 2-phenylethylacetate (2-PEAc), from L-phenylalanine (L-phe) with yeasts was investigated. The hydrophobicity of the products leads to product inhibition, which can be compensated by in situ product removal (ISPR). An organophilic pervaporation unit, equipped with a polyoctylmethylsiloxane (POMS) membrane, was coupled via a bypass to a bioreactor and proved to be a suitable technique for the in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Examples of successful approaches for the in situ recovery of inhibitory biomolecules include solvent extraction [20,23,24], adsorption [25][26][27], gas stripping [28], vacuum stripping [29], and membrane pervaporation [30,31]. Meanwhile, whereas in situ recovery strategies have been demonstrated as effective for improving the bioproduction of other aromatic compounds (e.g., 2-phenylethanol, phydroxystyrene, (S)-styrene oxide, and benzaldehyde) [32][33][34][35][36][37], their application to bio-derived styrene has not yet been reported. Moreover, whereas said prior studies have predominantly focused on single step biotransformations, the alternative focus here on de novo biosynthesis directly from renewable glucose presents new challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of successful approaches for the in situ recovery of inhibitory biomolecules include solvent extraction [20,23,24], adsorption [25][26][27], gas stripping [28], vacuum stripping [29], and membrane pervaporation [30,31]. Meanwhile, whereas in situ recovery strategies have been demonstrated as effective for improving the bioproduction of other aromatic compounds (e.g., 2-phenylethanol, phydroxystyrene, (S)-styrene oxide, and benzaldehyde) [32][33][34][35][36][37], their application to bio-derived styrene has not yet been reported. Moreover, whereas said prior studies have predominantly focused on single step biotransformations, the alternative focus here on de novo biosynthesis directly from renewable glucose presents new challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The production of 2-phenylethanol and its ester 2-phenylethyl acetate by various yeasts has been relatively well studied (Alber- Cardillo, Servi, & Zucchi, 1994;Etschmann, Bluemke, Sell, & Schrader, 2002;Etschmann & Schrader, 2006;Etschmann, Sell, & Schrader, 2003, 2005Huang, Lee, & Chou, 2000;Stark, Munch, Sonnleitner, Marison, & Stockar von, 2002;Wittmann, Hans, & Bluemke, 2002). However, the production of other aroma-active, yet commercially valuable esters of 2-phenylethanol, such as 2-phenylethyl esters of C3-C8 fatty acids, has received no or little research attention.…”
Section: Introductionmentioning
confidence: 99%
“…Etschmann and Schrader (2006) achieved the highest 2-PE concentration (10.2 g/L overall) reported by using K. marxianus CBS 600. Other ISPR techniques such as microcapsulation (Serp et al, 2003;Stark et al, 2003); and organophilic pervaporation (Etschmann et al, 2005) have also been reported.…”
mentioning
confidence: 99%